2016
DOI: 10.1097/01.sa.0000504595.97213.42
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Perioperative Medication Errors and Adverse Drug Events

Abstract: Background-The purpose of this study is to assess the rates of perioperative medication errors (MEs) and adverse drug events (ADEs) as percentages of medication administrations, evaluate their root causes, and formulate targeted solutions to prevent them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 14 publications
0
46
1
1
Order By: Relevance
“…Although medication error self-reporting has improved at our institution, reported error rates (1.56/ 1000 anesthetics) remain much lower than those reported with prospective observational data (84 errors/ 1000 anesthetics at our institution or 552 errors/1000 anesthetics at others) (6). Thus, it is likely that errors continue to be underreported.…”
Section: Limitationscontrasting
confidence: 42%
See 1 more Smart Citation
“…Although medication error self-reporting has improved at our institution, reported error rates (1.56/ 1000 anesthetics) remain much lower than those reported with prospective observational data (84 errors/ 1000 anesthetics at our institution or 552 errors/1000 anesthetics at others) (6). Thus, it is likely that errors continue to be underreported.…”
Section: Limitationscontrasting
confidence: 42%
“…This often occurs without added safety mechanisms such as computer decision support, pharmacy review, or independent double checks, which are standard in other health care arenas. A recent prospective observational study by Nanji et al (6) reported a high rate of perioperative medications errors by anesthesiologists, one in every 20 medication administrations. Pediatric patients were excluded from their observations, a population which The Joint Commission estimates is at a three times higher risk for medication-related adverse events (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Thus perioperative ADRs are usually underreported [20] . Therefore, it is important that drugs with a well-known safety profile are being used in this most crucial period [21] . Our study pointed out that the most common surgery related drugs that were used belonged to the classes of analgesics, antibiotics, antiemetics and gastroprotectants.…”
Section: Resultsmentioning
confidence: 99%
“…Even after 15 years of patient safety initiatives, recent research has found that roughly one in two surgeries had a medication error and/or an adverse drug event (Nanji, Patel, Shaikh, Seger, & Bates, 2016) and more than 12 million patients each year experience a diagnostic error in outpatient care, half of which are estimated to have the potential to cause harm (Singh, Meyer, & Thomas, 2014). On the other side, there is 1.3 million estimated reduction in hospital-acquired conditions (2011)(2012)(2013) as a result of the federal Partnership for Patients initiative (Agency for Healthcare Research and Quality, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%